(untitled) (Світ фінансів, 2017)
Метлушко О. В. Застосування андеррайтингу у банківській практиці. Розкривається економічний зміст терміна “андеррайтинг”. Досліджено світовий та вітчизняний досвід надання банками послуг з розміщення цінних паперів. Окреслено перспективи здійснення операцій комерційних банків з андеррайтингу. Metlushko O. The application of underwriting in bank practice. The economic content of the term “underwriting” is revealed. Global and home experience in offering banking services of placing the securities is examined. The perspectives of underwriting realization by commercial banks are determined.